Manufacturing method of laminate
Patent Information
- Application Number
- JP2020197257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-27
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-11-27
AI Technical Summary
【0010】 本発明によれば、高い弾性率、低い線熱膨張係数及び優れた耐久性を兼ね備えた積層体を提供することができる。
Smart Images

Figure 0007635537000005 
Figure 0007635537000006 
Figure 0007635537000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a laminate. Specifically, the present invention relates to a method for producing a laminate including a fine fibrous cellulose-containing layer. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products.
[0003] As fibrous cellulose, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. In addition, sheets made of such fine fibrous cellulose and composite sheets containing fine fibrous cellulose-containing sheets and resins have been developed. It is known that in sheets and composite sheets containing fine fibrous cellulose, the number of contact points between fibers increases, and thus the strength of the obtained sheets and composite sheets is greatly improved.
[0004] For example, Patent Documents 1 to 4 disclose composite sheets in which a layer containing fine fibrous cellulose and a resin layer are laminated. Patent Document 1 discloses a regenerated cellulose / resin laminated composite having a transparent film layer made of regenerated cellulose and two transparent amorphous resin layers made of at least one resin selected from the group consisting of polyacrylate resins and polycarbonate resins. Patent Document 2 discloses a method for producing a fiber-resin composite, which includes a step of applying a liquid composition containing cellulose nanofibers and a solvent to a substrate, a step of removing the solvent from the liquid composition, and a step of compounding the substrate after the solvent has been removed with the resin.
[0005] Patent Document 3 discloses a housing formed of a prepreg plate including a cellulose nanofiber layer formed by bonding cellulose nanofibers to the surface of a woven fabric made of multi-fiber yarn, and a resin layer adjacent to the nanofiber layer. Patent Document 4 discloses a laminate including a polycarbonate resin layer and a cellulose fiber layer, in which the thickness of the polycarbonate resin layer is 1.4 times or more the thickness of the cellulose fiber layer. In Patent Document 4, the laminate is formed by laminating the polycarbonate resin layer and the cellulose fiber layer, and a part of the cellulose fiber layer is exposed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-016066 A [Patent Document 2] JP 2017-222786 A [Patent Document 3] JP 2017-170829 A [Patent Document 4] JP 2010-023275 A Summary of the Invention [Problem to be solved by the invention]
[0007] In a composite sheet including a fine fibrous cellulose-containing sheet and a resin layer, it is desirable to obtain a laminate having a high elastic modulus and a low linear thermal expansion coefficient by laminating the fine fibrous cellulose-containing sheet and the resin layer. In addition, such a laminate may be required to have durability. Therefore, the present inventors have carried out investigations with the aim of providing a laminate having a high elastic modulus, a low coefficient of linear thermal expansion, and excellent durability. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the present inventors have found that in a process for producing a laminate comprising a fine fibrous cellulose-containing layer and a resin layer, a laminate having strength, dimensional stability and durability can be obtained by injecting molten resin into a mold in which a fine fibrous cellulose-containing sheet is arranged, and then solidifying the molten resin to encapsulate the fine fibrous cellulose-containing sheet with a resin component.
[0009] [1] A step of injecting a molten resin into a mold in which a sheet containing fibrous cellulose having a fiber width of 1000 nm or less is arranged; and solidifying the molten resin, A method for producing a laminate, wherein in the laminate, a sheet containing fibrous cellulose is in a state of being encapsulated by a resin component. [2] The method for producing a laminate according to [1], wherein the fibrous cellulose is unevenly distributed in a non-exposed region near the surface layer in the thickness direction of the laminate. [3] In the step of injecting the molten resin, the sheets containing fibrous cellulose are arranged along both sides of the inner wall of the mold so as to face each other, The method for producing a laminate according to [1] or [2], wherein at least a portion of the molten resin is filled between opposing sheets containing fibrous cellulose. [4] The method for producing a laminate according to any one of [1] to [3], wherein in the step of injecting the molten resin, the sheet containing fibrous cellulose is fixed to the inner wall of the mold via a resin sheet. [5] The method for producing a laminate according to any one of [1] to [4], wherein the area of the maximum surface of the laminate is larger than the area of the maximum surface of the sheet containing fibrous cellulose. [6] The method for producing a laminate according to any one of [1] to [5], wherein in the laminate, edges of the sheet containing fibrous cellulose are encapsulated with a resin component derived from the molten resin. [7] The method for producing a laminate according to any one of [1] to [6], further comprising the step of covering exposed areas of the sheet containing fibrous cellulose after the step of solidifying the molten resin. [8] The method for producing a laminate according to any one of [1] to [7], wherein the molten resin comprises an alloy resin containing a polycarbonate resin and an acrylic resin. Effect of the Invention
[0010] According to the present invention, it is possible to provide a laminate having a high elastic modulus, a low coefficient of linear thermal expansion, and excellent durability. [Brief description of the drawings]
[0011] [Figure 1] 1(a) and (b) are schematic diagrams illustrating a method for producing a laminate. [Diagram 2] 2(a) and (b) are schematic diagrams illustrating the configuration of the laminate. [Diagram 3] 3(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 4] 4(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Diagram 5] 5(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 6] 6(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 7] 7(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 8] 8(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 9] 9(a) and (b) are cross-sectional views illustrating the configuration of the laminate. [Figure 10] FIG. 10 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Figure 11] FIG. 11 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. [Figure 12] 12(a) and (b) are cross-sectional views illustrating the structure of the laminate. [Figure 13] 13(a) and (b) are cross-sectional views illustrating the structure of a laminate obtained in a comparative example. [Figure 14] 14(a) and (b) are cross-sectional views illustrating the structure of a laminate obtained in a comparative example. [Figure 15] 15(a) and (b) are cross-sectional views illustrating the configuration of a laminate obtained in a comparative example. [Figure 16] 16(a) and (b) are cross-sectional views illustrating the configuration of a laminate obtained in a comparative example. [Figure 17] 17(a) and (b) are cross-sectional views illustrating the structure of a laminate obtained in a comparative example. [Figure 18] 18(a) and (b) are cross-sectional views illustrating the configuration of a laminate obtained in a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the following, preferred embodiments of the present invention will be described in detail. The following description of the components may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.
[0013] (Method of manufacturing laminate) One embodiment of the present invention is a method for producing a laminate. The method for producing a laminate of this embodiment includes the steps of injecting a molten resin into a mold in which a sheet containing fibrous cellulose having a fiber width of 1000 nm or less is disposed, and solidifying the molten resin. In the laminate produced by the method for producing a laminate of the present invention, the sheet containing fibrous cellulose is in a state of being encapsulated by the resin component. In this specification, fibrous cellulose having a fiber width of 1000 nm or less is sometimes referred to as fine fibrous cellulose or CNF.
[0014] Fig. 1 is a schematic diagram for explaining the method for producing a laminate of this embodiment. As shown in Fig. 1(a), in the method for producing a laminate, first, a sheet containing fibrous cellulose having a fiber width of 1000 nm or less (fine fibrous cellulose-containing sheet 10) is placed in a mold 50. At this time, a laminating material may be laminated on the fine fibrous cellulose-containing sheet 10. The laminating material is preferably a resin sheet, and Fig. 1(a) illustrates a resin sheet 20 as an example of the laminating material.
[0015] As shown in FIG. 1, the mold 50 forms a void. The void may be formed from a series of mold components, or may be formed by combining a set of mold components. In FIG. 1, a set of molds 50 is formed by combining a mold component having a recess and a mold component having a protrusion. In this case, a mold component having a recess and a mold component having a protrusion are combined and joined to form one internal void. The shape of the mold component is not particularly limited as long as a void is formed inside the mold. For example, a mold may be formed by combining a mold component having a recess and a mold component having a recess.
[0016] When the fine fibrous cellulose-containing sheet 10 is disposed in the mold 50, it is preferable to fix the fine fibrous cellulose-containing sheet 10 in the mold 50 using a fixing means. In FIG. 1, the fine fibrous cellulose-containing sheet 10 and the resin sheet 20 are fixed in the gap of the mold 50 using a fixing member 52. Examples of the fixing member 52 include a heat-resistant tape, a clamping mechanism, a hook or pin for hanging, an electrostatic adsorption device, and a vacuum suction device. When the mold 50 is composed of a set of mold components, it is preferable to assemble the mold 50 after fixing the fine fibrous cellulose-containing sheet 10 using a fixing means.
[0017] When the fine fibrous cellulose-containing sheet 10 is disposed in the mold 50, its fixing position can be adjusted appropriately. For example, the fine fibrous cellulose-containing sheet 10 may be fixed on the mold plane of the mold 50, or the fine fibrous cellulose-containing sheet 10 may be fixed away from the mold plane. In this way, by appropriately adjusting the fixing position of the fine fibrous cellulose-containing sheet 10 in the gap of the mold 50, the arrangement position of the fine fibrous cellulose-containing sheet in the obtained laminate 100 can be controlled. In this specification, the mold plane is the surface that constitutes the maximum surface of the gap formed by assembling the mold. For example, when the mold is a combination of a mold component having a recess and a mold component having a protrusion, the mold plane is the bottom surface of the recess if the mold component has a recess, and is the top surface of the protrusion if the mold component has a protrusion.
[0018] After the fine fibrous cellulose-containing sheet 10 is fixed in the gap formed by the mold 50, a step of injecting a molten resin into the gap of the mold 50 is provided. At this time, the molten resin is preferably injected from the injection port 51 of the mold 50, and the molten resin is injected at a predetermined pressure. The position of the injection port 51 in the mold 50 is not particularly limited. For example, as shown in FIG. 1, the injection port 51 may be provided in the vicinity of a fixing member provided on the upper side. The injection port 51 may be provided at a plurality of positions in the mold 50. In the step of injecting the molten resin, it is preferable to appropriately adjust the temperature of the molten resin (melting temperature of the resin during molding), the clamping force during molding, the retention time after the injection of the molten resin (retention time during molding), the mold temperature when injecting the molten resin (mold temperature during molding), and the like.
[0019] The pressure at which the molten resin is injected is, for example, preferably 10 MPa to 500 MPa, more preferably 50 MPa to 400 MPa, and even more preferably 100 MPa to 300 MPa. The resin melting temperature during molding is, for example, preferably from 100 to 400°C, more preferably from 150 to 400°C, and even more preferably from 200 to 400°C. The mold clamping force during molding is, for example, preferably 200 kN to 100,000 kN, more preferably 500 kN to 50,000 kN, and even more preferably 1,000 kN to 10,000 kN. The retention time during molding is, for example, preferably from 0.1 to 600 seconds, more preferably from 1 to 300 seconds, and even more preferably from 10 to 60 seconds. The mold temperature during molding is, for example, preferably from 100 to 400°C, more preferably from 100 to 300°C, and even more preferably from 150 to 250°C.
[0020] Examples of the molten resin include resins obtained by melting polycarbonate resin, polyolefin resin, polyimide resin, polystyrene resin, acrylic resin, etc. The acrylic resin is preferably at least one selected from polyacrylonitrile and poly(meth)acrylate. Among them, the molten resin is preferably a molten resin containing at least one selected from polycarbonate resin and acrylic resin as a main component, and is particularly preferably a molten resin containing polycarbonate resin as a main component. The molten resin may be a resin obtained by melting an alloy resin containing polycarbonate resin and acrylic resin. When an alloy resin is used, the flexural modulus of the laminate tends to be higher and the linear thermal expansion coefficient tends to be smaller.
[0021] After the step of injecting the molten resin, a step of solidifying the molten resin is provided. In the step of solidifying the molten resin, the resin may be solidified, for example, by lowering the mold temperature. In this case, the mold temperature in the step of solidifying the molten resin is preferably adjusted appropriately depending on the type of molten resin injected, and is preferably set to, for example, less than 150°C, more preferably 130°C or less, and even more preferably 110°C or less. In this way, the laminate 100 is formed in the mold 50.
[0022] In addition, the process of solidifying the molten resin may be an active energy ray irradiation process when the molten resin used is an active energy ray curable resin. In this case, examples of the active energy ray include ultraviolet rays, electron beams, visible rays, X-rays, and ion beams. In addition, the process of solidifying the molten resin may be a heating process when the molten resin used is a thermosetting resin.
[0023] After the molten resin is solidified, the mold 50 is removed from the laminate 100 to obtain the laminate 100. At this time, the fixing member 52 may remain in the laminate 100, or the fixing member 52 may be removed from the laminate 100 together with the mold 50.
[0024] As described above, the method for producing the laminate of this embodiment is a method for producing a laminate by the injection molding method as described above. The method for producing the laminate of this embodiment may be an injection compression molding method. The injection compression molding method is a molding method also called a coining molding method, a stamping molding method, a compression-filling molding method, and a hybrid molding method. In the injection compression molding method, a compression step is provided during and / or after the molten resin is injected. By providing a compression step, it is also possible to obtain a thinner laminate with less internal residual stress.
[0025] In this embodiment, in the laminate obtained through the above-mentioned manufacturing method, the fine fibrous cellulose-containing sheet is in a state of being encapsulated by the resin component. That is, the manufacturing method of the laminate of this embodiment is a manufacturing method of a laminate in which the fine fibrous cellulose-containing sheet is encapsulated by the resin component. The state in which the fine fibrous cellulose-containing sheet is encapsulated by the resin component means that no part of the fine fibrous cellulose-containing sheet is exposed on the surface, and the periphery is covered by at least one type of resin. The resin component is mainly a resin used during injection molding, and the resin component may be made of the resin used during injection molding, but a part of the resin component may be a component derived from another resin member. For example, the other resin member may be a resin sheet previously laminated on the fine fibrous cellulose-containing sheet, or a cover resin that covers the exposed part of the fine fibrous cellulose-containing sheet after forming the laminate. That is, the resin component includes, in addition to the resin injected into the mold during injection molding, a resin component derived from the resin sheet previously laminated, and a resin component used when heat-sealing the exposed end of the fine fibrous cellulose-containing sheet in a later process.
[0026] The laminate produced by the method for producing a laminate of the present embodiment is excellent in strength and dimensional stability because it contains a fine fibrous cellulose-containing sheet. Specifically, the laminate obtained by the method for producing a laminate of the present embodiment has a high elastic modulus and a low coefficient of linear thermal expansion.
[0027] The flexural modulus of the laminate obtained by the manufacturing method of this embodiment is preferably greater than 2.2 GPa, more preferably 2.3 GPa or more, even more preferably 2.5 GPa or more, even more preferably 3.0 GPa or more, even more preferably 3.5 GPa or more, and particularly preferably 4.0 GPa or more. The flexural modulus of the laminate is a value measured in accordance with JIS K 7171:2016 under the conditions of a support distance of 64 mm and a deflection rate of 2 mm / min. At this time, the test piece is a test piece of 80 mm in length x 10 mm in width, and the test temperature is 23°C. The flexural modulus is calculated from the slope of the stress-strain curve between strains of 0.0005 to 0.0025. A universal material testing machine can be used as a measuring device for the flexural modulus, and for example, Tensilon RTC-1250A manufactured by A&D Co., Ltd. can be used.
[0028] The flexural modulus of the laminate obtained by the manufacturing method of this embodiment at high temperatures is preferably greater than 2.0 GPa, more preferably 2.1 GPa or more, even more preferably 2.3 GPa or more, even more preferably 2.5 GPa or more, even more preferably 3.0 GPa or more, and particularly preferably 4.0 GPa or more. The flexural modulus of the laminate at high temperatures is a value measured under the conditions of a support distance of 64 mm and a deflection rate of 2 mm / min in accordance with JIS K 7171:2016 except that the test temperature is 80°C. At this time, the test piece is a test piece with a length of 80 mm x width of 10 mm, and the test temperature is 80°C. The flexural modulus is calculated from the slope of the stress-strain curve between strains of 0.0005 to 0.0025. A universal material testing machine can be used as a measuring device for the flexural modulus, and for example, Tensilon RTC-1250A manufactured by A&D Co., Ltd. can be used.
[0029] The linear thermal expansion coefficient of the laminate obtained by the manufacturing method of this embodiment is preferably 70 ppm / K or less, more preferably 65 ppm / K or less, even more preferably 60 ppm / K or less, even more preferably 55 ppm / K or less, and particularly preferably 50 ppm / K or less. The linear thermal expansion coefficient of the laminate is a value calculated by measuring the length change of a test piece having a length of 50 mm and a width of 10 mm under conditions of a temperature range of 23 to 90 ° C. and a heating rate of 5 ° C. / min, and dividing the length change in a temperature range of 30 to 80 ° C. by the temperature change. A thermomechanical analyzer can be used to measure the length change, and for example, TMA / SS6100 manufactured by Seiko Instruments Inc. can be used.
[0030] Furthermore, the laminate produced by the laminate producing method of this embodiment exhibits excellent durability because the fine fibrous cellulose-containing sheet is encapsulated by the resin component. In this specification, the durability of the laminate can be judged to be good by observing the appearance of the laminate after immersing it in warm water, and if there is no change in the appearance of the laminate and the interlayer adhesion is maintained. Specifically, the laminate is immersed in warm water at a temperature of 60°C for 24 hours, and then the appearance of the laminate is observed. Even when the laminate obtained in this embodiment is immersed in warm water for a long time, the laminate does not expand, and the occurrence of delamination is suppressed.
[0031] The laminate produced by the laminate producing method of the present embodiment is also excellent in durability at high temperatures. In this specification, the durability of the laminate at high temperatures can be judged to be good if the appearance of the laminate is not changed after the laminate is exposed to high temperatures and the interlayer adhesion is maintained. Specifically, the laminate is left in a thermostatic chamber at a temperature of 110° C. under an air atmosphere for 720 hours, and then the appearance of the laminate is observed. Even when the laminate obtained in this embodiment is exposed to high temperatures for a long time, no defects are observed in the laminate and the occurrence of delamination is suppressed.
[0032] The laminate produced by the laminate production method of the present embodiment has excellent transparency and its yellowness is suppressed to a low level. Specifically, the haze of the laminate is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. The yellowness (YI value) of the laminate is preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. The haze of the laminate is a value measured using a haze meter in accordance with JIS K 7136:2000. The yellowness (YI value) of the laminate is a value measured using a color meter in accordance with JIS K 7373:2006.
[0033] The total light transmittance of the laminate is preferably 20% or more, more preferably 40% or more, even more preferably 60% or more, even more preferably 80% or more, and particularly preferably 85% or more. The upper limit of the total light transmittance of the laminate is not particularly limited, and may be, for example, 100%. Here, the total light transmittance of the laminate is, for example, a value measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7361-1:1997.
[0034] As described above, when the fine fibrous cellulose-containing sheet 10 is disposed in the mold 50, the position of the fine fibrous cellulose-containing sheet in the obtained laminate 100 can be controlled by appropriately adjusting the fixing position. That is, the uneven distribution area of the fine fibrous cellulose in the laminate 100 can be adjusted. In the manufacturing method of this embodiment, the fine fibrous cellulose-containing sheet 10 may be disposed on the center plane in the thickness direction of the void portion formed by the mold 50. In this case, the obtained laminate 100 has a configuration as shown in FIG. 2(a), and the cross section of the laminate 100 has a configuration as shown in FIG. 3. In FIGS. 2 and 3, the laminate 100 has the fine fibrous cellulose-containing sheet 10 and the resin layer 30, and the fine fibrous cellulose-containing sheet 10 is embedded in the resin layer 30. FIG. 3(a) is a cross-sectional view of the laminate 100, showing the layer configuration in a cross section parallel to the length direction (the direction of L in FIG. 2(a)). Fig. 3(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction (W direction in Fig. 2(a)). The cross section is a plane passing through the center point of the laminate 100, and is a plane that appears when cut in the thickness direction. In addition, the diagrams explaining the structure of the laminate in this specification are drawn so that the layer structure can be easily understood, and therefore the thickness and thickness ratio of each layer are not necessarily the same as those in the actual laminate.
[0035] In the manufacturing method of this embodiment, it is preferable to arrange the fine fibrous cellulose-containing sheet 10 along the plane of the mold 50. For example, the fine fibrous cellulose-containing sheet 10 may be arranged at a predetermined distance from the plane of the mold so as not to contact the plane of the mold. In this case, the molten resin also flows between the fine fibrous cellulose-containing sheet 10 and the mold 50, so that the cross section of the obtained laminate 100 has a structure as shown in FIG. 4. FIG. 4(a) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 4(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction.
[0036] In addition, when the fine fibrous cellulose-containing sheet 10 is arranged along the plane of the mold 50, another sheet may be arranged on the plane of the mold, and the fine fibrous cellulose-containing sheet 10 may be arranged thereon. In this case, the cross section of the obtained laminate 100 has a configuration as shown in FIG. 5. In FIG. 5, the fine fibrous cellulose-containing sheet 10 is in a state of being laminated on the resin sheet 20, and the fine fibrous cellulose-containing sheet 10 is arranged on the inner side in the thickness direction of the laminate 100. FIG. 5(a) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 5(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction. In the laminate 100 obtained as described above, the fibrous cellulose is unevenly distributed in the non-exposed region, which is the surface near region in the thickness direction of the laminate. In this specification, the surface near region in the thickness direction of the laminate refers to a region that is present in an area from the surface of the laminate to 30% of the total thickness of the laminate, and excluding the exposed outermost surface (the outermost surface of the laminate). In this way, by unevenly distributing the fibrous cellulose in the non-exposed region, which is the surface near region in the thickness direction of the laminate, the bending modulus of the laminate can be more effectively increased.
[0037] In addition, when the fine fibrous cellulose-containing sheet 10 is arranged in the mold 50, it is also preferable to arrange a plurality of fine fibrous cellulose-containing sheets 10 in the mold 50. For example, the fine fibrous cellulose-containing sheets 10 can be arranged so as to face each other along both sides of the mold inner wall (mold plane). In this case, at least a part of the molten resin is filled between the facing fine fibrous cellulose-containing sheets. Note that a part of the molten resin may be filled between the fine fibrous cellulose-containing sheet and the mold inner wall (mold plane). The cross section of the laminate 100 obtained in this manner has a configuration as shown in FIG. 6. FIG. 6(a) is a cross section of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 6(b) is a cross section of the laminate 100, showing the layer structure in a cross section parallel to the width direction. Note that the fine fibrous cellulose-containing sheets are preferably arranged evenly on one side and the other side of the laminate. "Evenly arranged on one side and the other side of the laminate" means that they are arranged approximately symmetrically with respect to a center line that divides the laminate in the thickness direction. In such a laminate, the variation in strength of the laminate can be suppressed, and the occurrence of warping in the laminate can be suppressed. When evaluating the warping of the laminate, the laminate is left to stand for 24 hours in an environment of a temperature of 23°C and a relative humidity of 50%, and then the laminate is observed. If no curvature is observed in the laminate and the shape immediately after production is maintained, it can be determined that the occurrence of warping is suppressed and the laminate is good.
[0038] In addition, when a plurality of fine fibrous cellulose-containing sheets 10 are arranged so as to face each other along both sides of the inner wall of a mold (mold plane), other sheets may be arranged on the plane of each mold, and the fine fibrous cellulose-containing sheets 10 may be arranged thereon. The cross section of the laminate 100 obtained in this manner has a configuration as shown in FIG. 7. FIG. 7(a) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 7(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction. In this way, by arranging the fibrous cellulose-containing sheets so as to face each other in the non-exposed region near the surface layer in the thickness direction of the laminate, the bending modulus of the laminate can be more effectively increased, and further, the occurrence of warping in the laminate can be suppressed.
[0039] As shown in FIG. 5 and FIG. 7, when the fine fibrous cellulose sheet 10 is disposed in the mold 50, the fine fibrous cellulose sheet 10 may be fixed to the inner wall of the mold (mold plane) via another sheet. In this case, the other sheet may preferably be a resin sheet, a metal sheet, or the like. Among them, the other sheet is preferably a resin sheet. That is, the fine fibrous cellulose sheet 10 is preferably fixed to the inner wall of the mold 50 via a resin sheet 20. The resin constituting the resin sheet is not particularly limited, but examples thereof include polycarbonate resin, polyolefin resin, polyimide resin, polystyrene resin, acrylic resin, and the like. Among them, the resin constituting the resin sheet is preferably at least one selected from polycarbonate resin and acrylic resin, and is particularly preferably polycarbonate resin. The resin constituting the resin sheet may be an alloy resin containing polycarbonate resin and acrylic resin.
[0040] The resin sheet 20 as described above may be present in a non-contact state with the fine fibrous cellulose-containing sheet 10. For example, the resin sheets 20 may be arranged on both sides of the inner wall of the mold (mold plane) so as to face each other, while the fine fibrous cellulose-containing sheet 10 may be arranged on the center plane in the thickness direction of the void portion formed by the mold 50. In this case, the cross section of the obtained laminate 100 has a configuration as shown in FIG. 8. FIG. 8(a) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 8(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction.
[0041] In the laminate 100 having the configuration shown in Figs. 2 to 8, the edge of the fine fibrous cellulose-containing sheet 10 is encapsulated with a resin component derived from the molten resin injected into a mold. In this specification, the edge of the fine fibrous cellulose-containing sheet 10 refers to the end face of the fine fibrous cellulose-containing sheet 10, the outer periphery of the fine fibrous cellulose-containing sheet 10, and the region indicated by hatched lines in Fig. 2(b). In the laminate obtained in this embodiment, the entire region of the edge of the fine fibrous cellulose-containing sheet is encapsulated with a resin component derived from the molten resin, so that the laminate has a high elastic modulus and a low coefficient of linear thermal expansion, and can exhibit excellent durability.
[0042] In addition, the manufacturing method of the laminate of this embodiment may further include a step of covering the exposed part of the fine fibrous cellulose-containing sheet 10 after the step of solidifying the molten resin. In such a case, before the covering step, at least a part of the edge of the fine fibrous cellulose-containing sheet 10 is not encapsulated by the resin component derived from the molten resin injected into the mold and is exposed from the laminate 100. Therefore, after forming the laminate 100 and removing the mold, the edge of the fine fibrous cellulose-containing sheet 10 that is exposed may be covered with a resin component to obtain a laminate in which the fine fibrous cellulose-containing sheet 10 is encapsulated with the resin component. The covering step may be a step of heat-sealing the exposed part of the fine fibrous cellulose-containing sheet 10 using a resin component, or a step of applying a molten resin to the exposed part of the fine fibrous cellulose-containing sheet 10. The resin component used in the covering step may be the same type of resin as the molten resin injected in the injection molding step, or may be a different type of resin. The cross section of the laminate 100 obtained through such steps has a configuration as shown in FIG. 9. FIG. 9(a) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the length direction. FIG. 9(b) is a cross-sectional view of the laminate 100, showing the layer structure in a cross section parallel to the width direction. In FIG. 9(b), the edge of the laminate 100 is covered with a coating resin 35 (cover resin). As a result, the edge of the fine fibrous cellulose-containing sheet 10 is also covered with a coating resin 35 (cover resin). In this way, by coating the fine fibrous cellulose-containing sheet 10 in a later process, it is also possible to make the sheet containing fibrous cellulose encapsulated with a resin component.
[0043] (Laminate) This embodiment may relate to a laminate manufactured by the laminate manufacturing method described above. The laminate has at least a layer containing fibrous cellulose having a fiber width of 1000 nm or less (also called a fine fibrous cellulose-containing layer or a fine fibrous cellulose-containing sheet) and a resin layer. In the laminate, the fine fibrous cellulose-containing layer is encapsulated with a resin component. In the laminate obtained in this embodiment, the entire region of the fine fibrous cellulose-containing layer is encapsulated with a resin component derived from a molten resin, so that the laminate has a high elastic modulus and a low linear thermal expansion coefficient, and can exhibit excellent durability.
[0044] Whether a laminate has been produced by the production method described in the present specification can be confirmed as follows. First, in the manufacturing process of the laminate, the layer containing fibrous cellulose having a fiber width of 1000 nm or less was disposed in the mold, and it can be confirmed by observing the morphology of the fiber layer part of the laminate with an electron microscope or the like to detect the presence of fibers having a fiber width of 1000 nm or less, and by analyzing the chemical composition with a Fourier transform infrared spectrophotometer or the like to detect a spectrum derived from cellulose. In addition, the state in which the layer containing fibrous cellulose having a fiber width of 1000 nm or less is encapsulated by the resin component can be confirmed by analyzing the chemical composition of the end part of the laminate with a Fourier transform infrared spectrophotometer or the like to detect a spectrum derived from the resin component. Furthermore, the manufacturing process of the laminate includes a step of injecting molten resin into the mold and a step of solidifying the molten resin, and it can be confirmed by the presence of an injection gate in the laminate, the shape of the end part of the laminate, good smoothness of the laminate surface, and the distribution of residual stress.
[0045] In the laminate, the area of the maximum surface of the laminate is preferably larger than the area of the maximum surface of the fine fibrous cellulose-containing sheet. This allows the fine fibrous cellulose-containing sheet to be embedded in the laminate. This allows for better durability. The area of the maximum surface of the laminate is a value calculated from the length x width of the laminate, and the area of the maximum surface of the fine fibrous cellulose-containing sheet is a value calculated from the length x width of the sheet. Of course, the thickness of the fine fibrous cellulose-containing sheet is thinner than the overall thickness of the laminate.
[0046] In the laminate, the fine fibrous cellulose-containing layer may be present in the center of the laminate in the thickness direction. The fine fibrous cellulose-containing layer may be present in the surface layer vicinity region in the thickness direction of the laminate. The surface layer vicinity region in the thickness direction of the laminate refers to a region that is present in a region from the surface of the laminate to 30% of the total thickness of the laminate, and refers to a region excluding the exposed outermost surface. In this way, by distributing fibrous cellulose in the non-exposed region in the surface layer vicinity region in the thickness direction of the laminate, the bending elastic modulus of the laminate can be more effectively increased. Furthermore, the fine fibrous cellulose-containing layer may be present in two or more layers in the laminate. For example, it is preferable that two layers of fine fibrous cellulose-containing layers are present in the surface layer vicinity region on the front side and the back side, respectively. In this way, by evenly distributing fine fibrous cellulose on one side and the other side of the laminate, the variation in strength of the laminate can be suppressed, and the occurrence of warping in the laminate can be suppressed.
[0047] The laminate may have a layer containing fibrous cellulose having a fiber width of 1000 nm or less, a resin layer, and a layer made of a resin sheet. The laminate may also have an optional layer as described below. In the laminate, each layer may be provided in one layer or in two or more layers. By the laminate having a layer made of a resin sheet, the durability and impact resistance of the laminate can be more effectively improved.
[0048] The total thickness of the laminate is preferably 1.0 mm or more, more preferably 2.0 mm or more, and even more preferably 3.0 mm or more. The upper limit of the total thickness of the laminate is not particularly limited, and may be, for example, 10 mm or less.
[0049] (Fine fibrous cellulose-containing layer) The layer containing fine fibrous cellulose (also referred to as a fine fibrous cellulose-containing layer) contains fibrous cellulose (fine fibrous cellulose) having a fiber width of 1000 nm or less. The fiber width of the fibrous cellulose is preferably 100 nm or less, more preferably 8 nm or less. This increases the transparency of the fine fibrous cellulose-containing layer, and increases the strength of the laminate when it is formed.
[0050] The fiber width of the fibrous cellulose can be measured, for example, by observation under an electron microscope. The average fiber width of the fibrous cellulose is, for example, 1000 nm or less. The average fiber width of the fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the average fiber width of the fibrous cellulose 2 nm or more, it is possible to suppress dissolution of the cellulose molecules in water, and to more easily exhibit the effect of improving the strength, rigidity, and dimensional stability of the fibrous cellulose. The fibrous cellulose is, for example, monofilamentous cellulose. The average fiber width of the fibrous cellulose is preferably within the above range, but the fine fibrous cellulose-containing layer may contain coarse fibers having a fiber width exceeding 1000 nm.
[0051] The average fiber width of fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y. For observation images that satisfy the above conditions, the width of the fibers that intersect with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average value of the read fiber widths is then determined as the average fiber width of the fibrous cellulose.
[0052] The fiber length of the fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, destruction of the crystalline region of the fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fibrous cellulose to an appropriate range. The fiber length of the fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.
[0053] The fibrous cellulose preferably has an I-type crystal structure. Here, the fact that the fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This can be expected to provide even more excellent performance in terms of heat resistance and low linear thermal expansion coefficient. The degree of crystallinity can be determined by measuring the X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0054] The axial ratio (fiber length / fiber width) of the fibrous cellulose is not particularly limited, but is preferably, for example, 20 to 10,000, and more preferably 50 to 1,000. By setting the axial ratio to the above lower limit or more, a sheet containing fine fibrous cellulose is easily formed. In addition, sufficient thickening is easily obtained when a solvent dispersion is produced. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fibrous cellulose is treated as an aqueous dispersion, handling such as dilution is facilitated.
[0055] The fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. In particular, fine fibrous cellulose having both crystalline and non-crystalline regions and a high axial ratio is realized by a method for producing fine fibrous cellulose, which will be described later.
[0056] The fibrous cellulose may have at least one of an ionic substituent and a nonionic substituent. From the viewpoint of improving the dispersibility of the fibrous cellulose in the dispersion medium and increasing the defibration efficiency in the defibration treatment, it is more preferable that the fibrous cellulose has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In addition, the nonionic substituent may include, for example, an alkyl group and an acyl group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group. Note that the fibrous cellulose does not need to be subjected to a treatment for introducing an ionic substituent.
[0057] The anionic group as the ionic substituent is preferably at least one selected from, for example, a phosphorus oxo acid group or a substituent derived from a phosphorus oxo acid group (sometimes simply referred to as a phosphorus oxo acid group), a carboxy group or a substituent derived from a carboxy group (sometimes simply referred to as a carboxy group), and a sulfone group or a substituent derived from a sulfone group (sometimes simply referred to as a sulfone group). Among them, the anionic group is more preferably at least one selected from a phosphorus oxo acid group and a carboxy group, and is particularly preferably a phosphorus oxo acid group. By introducing a phosphorus oxo acid group such as a phosphoric acid group or a phosphorous acid group as the anionic group, for example, even under alkaline conditions or acidic conditions, the dispersibility of the fibrous cellulose can be further improved, and the strength of the fine fibrous cellulose-containing sheet can be increased, and as a result, the strength of the laminate can be increased. In addition, by introducing a phosphorus oxo acid group such as a phosphoric acid group or a phosphorous acid group, the transparency of the resulting laminate can be more effectively increased and yellowing can be suppressed.
[0058] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). The phosphorus oxoacid group is, for example, a divalent functional group obtained by removing a hydroxyl group from phosphoric acid. Specifically, it is a group represented by -PO3H2. The substituent derived from the phosphorus oxoacid group includes a salt of the phosphorus oxoacid group, a phosphorus oxoacid ester group, and the like. The substituent derived from the phosphorus oxoacid group may be contained in the fibrous cellulose as a group in which a phosphoric acid group is condensed (for example, a pyrophosphate group). The phosphorus oxoacid group may be, for example, a phosphorous acid group (phosphonic acid group), and the substituent derived from the phosphorus oxoacid group may be a salt of the phosphorous acid group, a phosphorous acid ester group, or the like.
[0059] [ka]
[0060] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). 1 ,α 2 ,...,α n and a of α' are O - The rest are either R or OR. Note that each α n and all of α' are O - Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n is preferably 1.
[0061] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0062] In addition, examples of the derivative group in R include, but are not limited to, functional groups in which at least one of functional groups such as a carboxy group, a hydroxy group, or an amino group is added to or substituted for the main chain or side chain of the above-mentioned various hydrocarbon groups. In addition, the number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set within an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine cellulose fibers.
[0063] β b+is a monovalent or higher cation made of an organic or inorganic substance. Examples of the monovalent or higher cation made of an organic substance include aliphatic ammonium or aromatic ammonium, and examples of the monovalent or higher cation made of an inorganic substance include, but are not limited to, ions of alkali metals such as sodium, potassium, or lithium, cations of divalent metals such as calcium or magnesium, or hydrogen ions. These may be used alone or in combination of two or more. Examples of the monovalent or higher cation made of an organic or inorganic substance include, but are not limited to, sodium or potassium ions, which are less likely to yellow when a fiber raw material containing β is heated and are easy to use industrially. In addition, β b+ may be an organic onium ion.
[0064] The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 0.10 mmol / g or more per 1 g (mass) of fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 5.20 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.50 mmol / g or less, and particularly preferably 3.00 mmol / g or less. By setting the amount of ionic substituent introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of fibrous cellulose. In addition, by setting the amount of ionic substituent introduced within the above range, it is possible to exhibit good properties in various applications such as a thickener for fibrous cellulose. Here, the denominator in the unit mmol / g is calculated based on the fact that the counter ion of the ionic substituent is a hydrogen ion (H + ) indicates the mass of fibrous cellulose.
[0065] The amount of ionic substituents introduced into the fibrous cellulose can be measured, for example, by neutralization titration, in which an alkali such as an aqueous sodium hydroxide solution is added to a slurry containing the obtained fibrous cellulose to determine the change in pH, thereby measuring the amount introduced.
[0066] 10 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 10 is obtained. In the titration curve shown in the upper part of Figure 10, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 10, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH with respect to the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 10, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0067] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0068] In measuring the amount of phosphorus oxo acid groups by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of phosphorus oxo acid groups may be lower than the actual amount, and an accurate value may not be obtained. For example, a suitable amount of drop and titration interval is preferably 10 to 50 μL of 0.1N sodium hydroxide solution titrated every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0069] 11 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing the first cellulose fibers having a carboxy group and the pH. The amount of carboxy groups introduced into the first cellulose fibers is measured, for example, as follows. First, a slurry containing the first cellulose fibers is treated with a strongly acidic ion exchange resin. If necessary, a defibration treatment similar to the defibration treatment step described below may be performed on the measurement target prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 11 is obtained. In the titration curve shown in the upper part of FIG. 11, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 11, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 11 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the slurry containing the first cellulose fiber to be titrated to calculate the amount of carboxyl groups introduced (mmol / g). The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) is the amount of substituents (hereinafter referred to as the amount of carboxy groups (acid type)) per 1 g of the mass of the first cellulose fibers.
[0070] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose with the cation C as the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0071] In measuring the amount of substituents by titration, if the titration interval of the sodium hydroxide aqueous solution is too short, the amount of substituents may be lower than it should be. Therefore, it is desirable to use an appropriate titration interval, for example, titrating 10 to 50 μL of 0.1 N sodium hydroxide aqueous solution every 5 to 30 seconds.
[0072] The content of fibrous cellulose is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 30% by mass or more, even more preferably 50% by mass or more, and particularly preferably 70% by mass or more, based on the total mass of the fine fibrous cellulose-containing layer. The content of fibrous cellulose may be 100% by mass based on the total mass of the fine fibrous cellulose-containing layer. In other words, the fine fibrous cellulose-containing layer may be a layer made of fine fibrous cellulose.
[0073] The thickness of one layer containing fine fibrous cellulose is preferably 20 μm or more, more preferably 40 μm or more, and even more preferably 60 μm or more. The thickness of one layer containing fine fibrous cellulose is preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 250 μm or less. Even if two or more layers containing fine fibrous cellulose are provided in the laminate, the thickness of each layer is preferably within the above range. By setting the thickness of the fine fibrous cellulose-containing layer within the above range, it is easy to obtain strength for reinforcing the laminate. In addition, the production efficiency of the fine fibrous cellulose-containing layer can be improved. Here, the thickness of one layer containing fine fibrous cellulose can be measured by cutting out a cross section of the laminate using, for example, an ultramicrotome UC-7 (manufactured by JEOL Co., Ltd.) and observing the cross section with an electron microscope.
[0074] The density of the fine fibrous cellulose-containing layer is 0.5 g / cm 3 It is preferable that the content is 1.0 g / cm or more. 3 More preferably, it is 1.2 g / cm or more. 3 More preferably, it is 1.4 g / cm or more. 3 The upper limit of the density of the fine fibrous cellulose-containing layer is not particularly limited, and is, for example, 3.0 g / cm. 3 By setting the density of the fine fibrous cellulose-containing layer within the above range, it becomes easier to obtain the strength required to reinforce the laminate. The density of the fine fibrous cellulose-containing layer is a value calculated by dividing the basis weight of the layer by the thickness.
[0075] The basis weight of one layer containing fine fibrous cellulose is 10 g / m 2 It is preferable that the thickness is 30 g / m or more. 2 More preferably, it is 50 g / m or more. 2 More preferably, it is 100 g / m or more. 2 It is particularly preferable that the basis weight of one fine fibrous cellulose-containing layer is 1500 g / m 2 It is preferable that the thickness is less than 750 g / m 2 More preferably, it is 500 g / m or less. 2 In the case where a plurality of fine fibrous cellulose-containing layers are provided, the total basis weight of the fine fibrous cellulose-containing layers is preferably 50 g / m or less. 2 It is preferable that the thickness is 100 g / m or more. 2 The total basis weight of the fine fibrous cellulose-containing layers is preferably 3000 g / m or more. 2 It is preferable that the thickness is less than 1500 g / m 2 More preferably, it is 1000 g / m or less. 2 The basis weight of one layer containing fine fibrous cellulose is more preferably 150 g / m or less. 2 or more, and 2The total basis weight of the fine fibrous cellulose-containing layer may be 300 g / m or more. 2 or more, and 2 or more. By increasing the basis weight of the fine fibrous cellulose-containing layer, the bending modulus of the laminate can be more effectively increased and the linear thermal expansion coefficient of the laminate can be further reduced. Here, the basis weight of the fine fibrous cellulose-containing layer is a value calculated according to the following method after cutting the layer using, for example, an ultramicrotome UC-7 (manufactured by JEOL) so that only the fiber layer remains. The weight of the fiber layer cut into a size of 2 cm square or more is measured, and the weight is divided by the area of the cut fiber layer to calculate the basis weight of the fiber layer.
[0076] The haze of the fine fibrous cellulose-containing layer is preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less. On the other hand, the lower limit of the haze of the fine fibrous cellulose-containing layer is not particularly limited, and may be, for example, 0%. Here, the haze of the fine fibrous cellulose-containing layer is a value measured by cutting the fine fibrous cellulose-containing layer with, for example, an ultramicrotome UC-7 (manufactured by JEOL) so that only the fine fibrous cellulose-containing layer remains, and using a haze meter (manufactured by Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7136:2000.
[0077] The total light transmittance of the fine fibrous cellulose-containing layer is, for example, preferably 85% or more, more preferably 90% or more, and even more preferably 91% or more. On the other hand, the upper limit of the total light transmittance of the fine fibrous cellulose-containing layer is not particularly limited, and may be, for example, 100%. Here, the total light transmittance of the fine fibrous cellulose-containing layer is a value measured using a haze meter (Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7361-1:1997 after cutting the layer using, for example, an ultramicrotome UC-7 (JEOL) so that only the fine fibrous cellulose-containing layer remains.
[0078] The fine fibrous cellulose-containing layer may contain optional components other than fine fibrous cellulose. Examples of optional components include hydrophilic polymers, hydrophilic low molecules, and organic ions. The fine fibrous cellulose-containing layer may contain one or more optional components selected from surfactants, coupling agents, inorganic layered compounds, inorganic compounds, leveling agents, preservatives, defoamers, organic particles, lubricants, antistatic agents, UV protection agents, dyes, pigments, stabilizers, magnetic powders, alignment promoters, plasticizers, dispersants, and crosslinking agents.
[0079] The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (excluding the above-mentioned cellulose fibers), and examples of the oxygen-containing organic compound include polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates, acrylic acid alkyl ester copolymers, urethane copolymers, cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.), and the like.
[0080] The hydrophilic low molecular weight compound is preferably a hydrophilic oxygen-containing organic compound, more preferably a polyhydric alcohol, such as glycerin, sorbitol, or ethylene glycol.
[0081] Examples of organic ions include tetraalkylammonium ions and tetraalkylphosphonium ions. Examples of tetraalkylammonium ions include tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions. Examples of tetraalkylphosphonium ions include tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions. Examples of tetrapropylonium ions and tetrabutylonium ions include tetra-n-propylonium ions and tetra-n-butylonium ions, respectively.
[0082] The end of the fine fibrous cellulose-containing layer may be covered with a coating resin (cover resin). Examples of the resin type used for the coating resin include the resin type used for the resin layer.
[0083] <Production process of fine fibrous cellulose> <Textile raw materials> Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP) and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, but may be deinked pulp made from waste paper. The pulp of this embodiment may be one of the above, or may be a mixture of two or more. Among the above pulps, wood pulp and deinked pulp are preferable from the viewpoint of availability. Among wood pulps, chemical pulp is more preferable, and kraft pulp and sulfite pulp are even more preferable, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of small decomposition of cellulose in the pulp and of obtaining long-fiber fine fibrous cellulose with a large axial ratio. The viscosity tends to be high when long-fiber fine fibrous cellulose with a large axial ratio is used.
[0084] As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of a fiber raw material containing cellulose, a fiber formed by a linear nitrogen-containing polysaccharide polymer such as chitin or chitosan can be used.
[0085] <Phosphorus oxo acid group introduction step> The process for producing fine fibrous cellulose preferably includes a phosphorus oxoacid group introduction step, which is a step of reacting at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing phosphorus oxoacid groups by reacting with hydroxyl groups possessed by a fiber raw material containing cellulose with the fiber raw material containing cellulose. This step results in the production of fibers into which phosphorus oxoacid groups have been introduced.
[0086] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.
[0087] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. Compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0088] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of the phosphoric acid include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium dihydrogen phosphate are more preferred.
[0089] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0090] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0091] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0092] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0093] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, various devices having heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0094] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).
[0095] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated in the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0096] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0097] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be repeated two or more times. By carrying out the phosphorus oxo acid group introduction step two or more times, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material. In the present embodiment, a preferred embodiment includes carrying out the phosphorus oxo acid group introduction step two times.
[0098] The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 0.10 mmol / g or more per gram (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 5.20 mmol / g or less per gram (mass) of fine fibrous cellulose, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of phosphorus oxoacid groups introduced within the above range, it is possible to easily fine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0099] <Carboxy group introduction step> The carboxyl group introduction process is carried out by subjecting a fiber raw material containing cellulose to an oxidation process such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or by treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride or a derivative thereof of a compound having a carboxylic acid-derived group.
[0100] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0101] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0102] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of pH 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). By further allowing sodium chlorite to coexist, aldehydes generated during the oxidation process can be efficiently oxidized to carboxyl groups. The TEMPO oxidation treatment may also be performed under conditions of pH 10 or more and 11 or less. Such a treatment is also called an alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be performed, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a cocatalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.
[0103] The amount of carboxyl groups introduced into the fiber raw material varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, the amount is preferably 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. Also, it is preferably 2.5 mmol / g or less, more preferably 2.20 mmol / g or less, and even more preferably 2.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, it may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose.
[0104] <Cleaning process> In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0105] <Alkaline treatment process> When producing fine fibrous cellulose, an alkali treatment may be carried out on the fiber raw material between the step of introducing an ionic substituent and the step of defibrating the fiber, which will be described later. The method of the alkali treatment is not particularly limited, but may be, for example, a method of immersing the fiber having an ionic substituent introduced therein in an alkali solution.
[0106] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0107] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The time for immersing the phosphorus oxo acid group-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is preferably, for example, from 100% by mass to 100,000% by mass, and more preferably from 1,000% by mass to 10,000% by mass, based on the absolute dry mass of the phosphorus oxo acid group-introduced fiber.
[0108] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the phosphorus oxo acid group-introduced fiber may be washed with water or an organic solvent after the ionic substituent introduction step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0109] <Acid treatment process> When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described later. For example, the step of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order.
[0110] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0111] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material.
[0112] <Defibrillation processing> The ionic substituent-introduced fibers are defibrated in a defibration process to obtain fine fibrous cellulose. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0113] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0114] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the ionic substituent-introduced fibers in a dispersion medium may contain solids other than the phosphorus oxo acid group-introduced fibers, such as urea having hydrogen bonding properties.
[0115] <Production process of fine fibrous cellulose-containing sheet> An example of a method for producing a fine fibrous cellulose-containing sheet is a method in which a fine fibrous cellulose-containing slurry obtained through the above-mentioned defibration process is made into paper or coated (applied) and then dried to form a fine fibrous cellulose-containing sheet.
[0116] The slurry used in the manufacturing process of the fine fibrous cellulose-containing sheet preferably further contains, for example, a hydrophilic polymer. This can further improve the transparency and mechanical strength of the sheet. The hydrophilic polymer may contain, for example, one or more types selected from the above-mentioned examples.
[0117] <Coating process> In the coating process, for example, a slurry containing fibrous cellulose is coated on a substrate, and the coated slurry is dried to form a sheet, which is then peeled off from the substrate to obtain a sheet. By using a coating device and a long substrate, the sheets can be produced continuously.
[0118] The material of the substrate used in the coating process is not particularly limited, but a substrate with high wettability to the composition (slurry) is better in that it can suppress the shrinkage of the sheet during drying, but it is preferable to select a substrate from which the sheet formed after drying can be easily peeled off. Among them, resin films or plates or metal films or plates are preferable, but are not particularly limited. For example, resin films or plates such as acrylic, polyethylene terephthalate, vinyl chloride, polystyrene, polypropylene, polycarbonate, polyvinylidene chloride, metal films or plates such as aluminum, zinc, copper, and iron plates, and those whose surfaces have been oxidized, stainless steel films or plates, brass films or plates, etc. can be used.
[0119] In the coating process, if the viscosity of the slurry is low and the slurry spreads on the substrate, a damming frame may be fixed on the substrate to obtain a sheet of a predetermined thickness and basis weight. The damming frame is not particularly limited, but it is preferable to select a frame that allows the end of the sheet to be easily peeled off after drying. From this viewpoint, a molded resin plate or metal plate is more preferable. In this embodiment, for example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, polypropylene plates, polycarbonate plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, stainless steel plates, brass plates, and the like can be used.
[0120] The coating machine for coating the substrate with the slurry is not particularly limited, and examples thereof include a roll coater, a gravure coater, a die coater, a curtain coater, an air doctor coater, etc. Since the thickness of the sheet can be made more uniform, a die coater, a curtain coater, and a spray coater are particularly preferred.
[0121] The slurry temperature and the ambient temperature when the slurry is applied to the substrate are not particularly limited, but are preferably, for example, 5°C to 80°C, more preferably 10°C to 60°C, even more preferably 15°C to 50°C, and particularly preferably 20°C to 40°C. If the application temperature is equal to or higher than the lower limit, the slurry can be applied more easily. If the application temperature is equal to or lower than the upper limit, the evaporation of the dispersion medium during application can be suppressed.
[0122] As described above, the coating step includes a step of drying the slurry coated on the substrate. The step of drying the slurry is not particularly limited, but may be performed, for example, by a non-contact drying method, a method of drying while restraining the sheet, or a combination of these.
[0123] The non-contact drying method is not particularly limited, but for example, a method of drying by heating with hot air, infrared rays, far infrared rays or near infrared rays (heat drying method), or a method of drying by vacuum (vacuum drying method) can be applied. The heat drying method and the vacuum drying method may be combined, but the heat drying method is usually applied. Drying by infrared rays, far infrared rays or near infrared rays can be performed using, for example, an infrared device, a far infrared device or a near infrared device, but is not particularly limited. The heating temperature in the heat drying method is not particularly limited, but is preferably, for example, 20°C or more and 150°C or less, and more preferably, 25°C or more and 105°C or less. If the heating temperature is set to the above lower limit value or more, the dispersion medium can be quickly volatilized. In addition, if the heating temperature is set to the above upper limit value or less, it is possible to suppress the cost required for heating and the discoloration of the fibrous cellulose due to heat.
[0124] <Paper making process> The papermaking process is carried out by making the slurry into paper using a papermaking machine. The papermaking machine used in the papermaking process is not particularly limited, but may be, for example, a continuous papermaking machine such as a fourdrinier type, a cylinder type, or an inclined type, or a multi-layer papermaking machine that combines these. In the papermaking process, a known papermaking method such as handmaking may be used.
[0125] The papermaking process is carried out by filtering the slurry with a wire, dehydrating the slurry to obtain a sheet in a wet paper state, and then pressing and drying the sheet. The filter cloth used for filtering and dehydrating the slurry is not particularly limited, but it is more preferable that, for example, fibrous cellulose does not pass through and the filtration speed does not become too slow. Such filter cloth is not particularly limited, but for example, a sheet, fabric, or porous membrane made of an organic polymer is preferable. The organic polymer is not particularly limited, but for example, a non-cellulose organic polymer such as polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), etc. are preferable. In this embodiment, for example, a porous membrane of polytetrafluoroethylene with a pore size of 0.1 μm to 20 μm, and a woven fabric of polyethylene terephthalate or polyethylene with a pore size of 0.1 μm to 20 μm are examples.
[0126] In the sheet forming process, a method for producing a sheet from the slurry can be performed, for example, by using a production apparatus including a water squeezing section in which a slurry containing fibrous cellulose is discharged onto an endless belt and the dispersion medium is squeezed out of the discharged slurry to produce a web, and a drying section in which the web is dried to produce a sheet. An endless belt is disposed between the water squeezing section and the drying section, and the web produced in the water squeezing section is transported to the drying section while still placed on the endless belt.
[0127] The method for producing a sheet from a slurry containing fine fibrous cellulose is not particularly limited, and examples thereof include a method using a production apparatus described in WO2011 / 013567. This production apparatus includes a water squeezing section in which a slurry containing fine fibrous cellulose is discharged onto an upper surface of an endless belt and the dispersion medium is squeezed out of the discharged slurry to produce a web, and a drying section in which the web is dried to produce a sheet. An endless belt is disposed between the water squeezing section and the drying section, and the web produced in the water squeezing section is transported to the drying section while still placed on the endless belt.
[0128] The dehydration method that can be used in this embodiment is not particularly limited, but includes dehydration methods that are commonly used in paper manufacturing, and is preferably a method of dehydrating with a roll press after dehydrating with a fourdrinier, cylinder, inclined wire, etc. In addition, the drying method is not particularly limited, but includes a method that is used in paper manufacturing, and is preferably a method such as a cylinder dryer, Yankee dryer, hot air drying, near-infrared heater, or infrared heater.
[0129] Methods for drying the slurry to form a sheet include, for example, heat drying, air drying, and reduced pressure drying. Pressurization may be performed in parallel with drying. The heating temperature is preferably about 50°C to 250°C. Within this temperature range, drying can be completed in a short time and discoloration and coloring can be suppressed. Pressurization is preferably 0.01 MPa to 5 MPa. Within this pressure range, the occurrence of cracks and wrinkles can be suppressed and the density of the fine fibrous cellulose-containing sheet can be increased.
[0130] When an optional component is added to the fine fibrous cellulose-containing sheet, it is preferable to uniformly mix the optional component in the fiber slurry to form a fine fibrous cellulose-containing sheet in which the optional component is dispersed. For example, if an oxygen-containing organic compound is mixed as an optional component in the fiber slurry, the drying proceeds gently in the process of forming a sheet by drying a thin layer of the fiber slurry obtained by making or applying the fiber slurry, and the fine fibrous cellulose-containing sheet can be prevented from cracking or wrinkling. As a result, a high-density, transparent film-like fine fibrous cellulose-containing sheet can be formed. The dehydration method used in the papermaking process is not particularly limited, but for example, a dehydration method normally used in the manufacture of paper can be mentioned. Among these, a method of dehydrating with a fourdrinier, a cylinder net, an inclined wire, or the like, and then further dehydrating with a roll press is preferable. In addition, the drying method used in the papermaking process is not particularly limited, but for example, a method used in the manufacture of paper can be mentioned. Among these, a drying method using a cylinder dryer, a Yankee dryer, a hot air dryer, a near-infrared heater, an infrared heater, or the like is more preferable.
[0131] (Resin layer) The resin layer is a layer formed by solidifying the molten resin injected into the mold in the above-mentioned laminate manufacturing method. The resin layer is a layer containing resin as a main component, and the resin content relative to the total mass of the resin layer is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The resin content relative to the total mass of the resin layer may be 100% by mass, and the resin layer may be a layer made of resin.
[0132] The thickness of the resin layer is preferably 1000 μm or more, more preferably 2000 μm or more, and even more preferably 3000 μm or more. The upper limit of the total thickness of the resin layer is not particularly limited, and may be, for example, 10 mm or less. In the case where the laminate has two or more resin layers, the total thickness of each layer is preferably within the above range. By setting the thickness of the resin layer within the above range, a laminate having a high elastic modulus is easily obtained. Here, the thickness of the resin layer constituting the laminate can be measured by, for example, cutting out a cross section of the laminate using an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope, a magnifying glass, or visually.
[0133] In this embodiment, since the fine fibrous cellulose-containing layer functions as a reinforcing layer for the resin layer, the thickness of the resin layer is preferably thicker than that of the fine fibrous cellulose-containing layer. If the total thickness of the resin layer is P and the total thickness of the fine fibrous cellulose-containing layer is Q, the value of P / Q is preferably 1.2 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. The value of P / Q is preferably 80 or less.
[0134] Examples of the resin contained in the resin layer include natural resins and synthetic resins. Examples of the natural resin include rosin resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0135] Examples of synthetic resins include polycarbonate resin, polyolefin resin, polyimide resin, polystyrene resin, acrylic resin, etc. The acrylic resin is preferably at least one selected from polyacrylonitrile and poly(meth)acrylate. Since the resin layer is a layer formed by solidifying a molten resin, it is preferable to use a thermoplastic resin as the molten resin. Among them, the synthetic resin is preferably at least one selected from polycarbonate resin and acrylic resin, and is particularly preferably polycarbonate resin. The synthetic resin may be an alloy resin containing polycarbonate resin and acrylic resin. When an alloy resin is used, the flexural modulus of the laminate tends to be higher and the linear thermal expansion coefficient tends to be smaller.
[0136] Examples of the polycarbonate constituting the resin layer include aromatic polycarbonate resins and aliphatic polycarbonate resins. Specific examples of these polycarbonate resins are known, and examples of such polycarbonate resins include the polycarbonate resins described in JP-A-2010-023275.
[0137] The resin layer may contain optional components other than the synthetic resin, such as fillers, pigments, dyes, and ultraviolet absorbers, which are known components used in the field of resin films.
[0138] (Resin sheet) The laminate may include a resin sheet (a layer made of a resin sheet) in addition to the resin layer. The resin sheet is a sheet that is disposed in a mold together with a fine fibrous cellulose-containing sheet in the manufacturing process of the laminate, and is distinguished from the resin layer formed from the molten resin injected in the injection molding process. However, in the manufacturing process of the laminate, a part or all of the resin sheet melts and becomes compatible with the molten resin injected in the injection molding process, and the interface between the resin layer and the resin sheet may not be clear. In such a case, it may be considered that the resin layer includes a layer made of a resin sheet. The resin type constituting the resin layer and the resin sheet may be the same type or different types. When the resin type constituting the resin layer and the resin sheet can be distinguished by the resin type, even if the interface between the resin layer and the resin sheet is not clear, it can be said that a layer made of a resin sheet exists in the laminate.
[0139] The resin constituting the resin sheet is not particularly limited, but examples thereof include polycarbonate resin, polyolefin resin, polyimide resin, polystyrene resin, acrylic resin, etc. The acrylic resin is preferably at least one selected from polyacrylonitrile and poly(meth)acrylate. Among them, the resin constituting the resin sheet is preferably at least one selected from polycarbonate resin and acrylic resin, and is particularly preferably polycarbonate resin. The resin constituting the resin sheet may be an alloy resin containing polycarbonate resin and acrylic resin.
[0140] The thickness of one layer made of a resin sheet is preferably 50 μm or more, more preferably 100 μm or more, and even more preferably 150 μm or more. The thickness of one layer made of a resin sheet is preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 300 μm or less. Even if two or more layers made of a resin sheet are provided in the laminate, the thickness of each layer is preferably within the above range.
[0141] In this way, when the laminate includes a resin sheet (a layer made of a resin sheet) in addition to the resin layer, the durability of the laminate can be more effectively improved. In addition, since a resin sheet according to a purpose can be arranged on the surface of the laminate, for example, a resin sheet can be used to improve chemical resistance, scratch resistance, and weather resistance.
[0142] The flexural modulus of the resin sheet is preferably 0.5 GPa or more, more preferably 1 GPa or more, and even more preferably 2 GPa or more. The flexural modulus of the resin sheet is a value measured in accordance with JIS K 7171:2016 under the conditions of a support distance of 64 mm and a deflection rate of 2 mm / min. In this case, the test piece is a test piece of 80 mm in length x 10 mm in width, and the test temperature is 23°C. The flexural modulus is calculated from the slope of the stress-strain curve between strains of 0.0005 to 0.0025. A universal material testing machine can be used as a measuring device for the flexural modulus, and for example, Tensilon RTC-1250A manufactured by A&D Co., Ltd. can be used.
[0143] The total light transmittance of the resin sheet is preferably 20% or more, more preferably 40% or more, even more preferably 60% or more, even more preferably 80% or more, and particularly preferably 85% or more. The upper limit of the total light transmittance of the resin sheet is not particularly limited, and may be, for example, 100%. Here, the total light transmittance of the resin sheet is, for example, a value measured using a haze meter (Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7361-1:1997.
[0144] The linear thermal expansion coefficient of the resin sheet is preferably 150 ppm / K or less, more preferably 100 ppm / K or less, and even more preferably 75 ppm / K or less. The linear thermal expansion coefficient of the resin sheet is a value calculated by measuring the change in length of a test piece having a length of 50 mm and a width of 10 mm under conditions of a temperature range of 23 to 90°C and a heating rate of 5°C / min, and dividing the change in length in a temperature range of 30 to 80°C by the change in temperature. A thermomechanical analyzer can be used to measure the change in length, and for example, TMA / SS6100 manufactured by Seiko Instruments Inc. can be used.
[0145] The resin sheet may contain optional components, such as fillers, pigments, dyes, and ultraviolet absorbing agents.
[0146] (arbitrary layer) The laminate may further include any layer other than the layers described above. Examples of the optional layer include an adhesive layer, an inorganic layer, a hard coat layer, an anti-fog layer, and an anti-glare layer.
[0147] <Adhesive layer> The laminate may further have an adhesive layer. In this case, the adhesive layer is preferably provided between the fine fibrous cellulose-containing layer and the resin layer, and the fine fibrous cellulose-containing layer may be firmly adhered to the resin layer via the adhesive layer.
[0148] The thickness of one adhesive layer is, for example, preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 2 μm or more. The thickness of one adhesive layer is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, even more preferably 20 μm or less, particularly preferably 10 μm or less, and most preferably 7 μm or less. When the thickness of one adhesive layer is the above-mentioned lower limit value or more, sufficient adhesion between the fine fibrous cellulose-containing layer and the resin layer is obtained. Here, the thickness of the adhesive layer constituting the laminate can be measured by, for example, cutting out a cross section of the laminate with an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope.
[0149] The adhesive layer preferably contains, as a main component, one or more adhesives selected from (meth)acrylic acid ester polymers, α-olefin copolymers, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyurethane, styrene-butadiene copolymers, polyvinyl chloride, epoxy resins, melamine resins, silicone resins, polycarbonate resins, polyethylene terephthalate resins, polyethylene naphthalate resins, polyethylene resins, polypropylene resins, polyimide resins, polystyrene resins, casein, natural rubber, and starch. Here, "as a main component" means that the adhesive layer contains 50% by mass or more of the total mass (100% by mass) of the adhesive layer. The (meth)acrylic acid ester polymer includes polymers obtained by graft polymerization of synthetic resins other than (meth)acrylic resins, such as epoxy resins and urethane resins, and copolymers obtained by copolymerization of (meth)acrylic acid esters and other monomers.
[0150] The adhesive layer may contain an adhesion aid. Examples of the adhesion aid include compounds containing at least one selected from an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, and a silanol group, and organosilicon compounds. Among them, the adhesion aid is preferably at least one selected from a compound containing an isocyanate group (isocyanate compound) and an organosilicon compound. Examples of the organosilicon compound include a silane coupling agent condensate and a silane coupling agent.
[0151] The content of the adhesion aid is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the adhesive contained in the adhesive layer, and is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, relative to 100 parts by mass of the adhesive contained in the adhesive layer. When the adhesion aid is an isocyanate compound, the content of the isocyanate compound is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 18 parts by mass or more, relative to 100 parts by mass of the adhesive contained in the adhesive layer. The content of the isocyanate compound is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the adhesive contained in the adhesive layer. When the adhesion aid is an organosilicon compound, the content of the organosilicon compound is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the adhesive contained in the adhesive layer. Also, the content of the organosilicon compound is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the adhesive contained in the adhesive layer.
[0152] When the adhesion aid is an isocyanate compound, the content of the isocyanate group contained in the adhesive layer is preferably 0.5 mmol / g or more, more preferably 0.6 mmol / g or more, even more preferably 0.8 mmol / g or more, and particularly preferably 0.9 mmol / g or more. The content of the isocyanate group contained in the adhesive layer is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, even more preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less.
[0153] The adhesive layer can be formed, for example, by applying an adhesive layer-forming composition to a fine fibrous cellulose-containing sheet. When applying the adhesive layer-forming composition, a roll coater, a bar coater, a gravure coater, a die coater, a curtain coater, an air doctor coater, or the like can be used. In addition, since such an adhesive layer is a layer that covers the surface of the fine fibrous cellulose-containing sheet, it may also be called a surface treatment layer.
[0154] <Inorganic layer> The laminate may further include an inorganic layer. The inorganic layer may be provided as the outermost layer of the laminate, or may be provided as a layer constituting the inner side of the laminate.
[0155] The material constituting the inorganic layer is not particularly limited, and examples thereof include aluminum, silicon, magnesium, zinc, tin, nickel, titanium; their oxides, carbides, nitrides, oxycarbides, oxynitrides, or oxycarbonitrides; or mixtures thereof. From the viewpoint of stably maintaining high moisture resistance, silicon oxide, silicon nitride, silicon oxide carbide, silicon oxynitride, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxide carbide, aluminum oxynitride, or mixtures thereof are preferred.
[0156] The method for forming the inorganic layer is not particularly limited. Generally, the methods for forming a thin film are roughly divided into chemical vapor deposition (CVD) and physical vapor deposition (PVD), and either method may be adopted. Specific examples of the CVD method include plasma CVD using plasma, and catalytic chemical vapor deposition (Cat-CVD) in which a material gas is catalytically decomposed by pyrolysis using a heated catalyst. Specific examples of the PVD method include vacuum deposition, ion plating, sputtering, and the like.
[0157] Atomic layer deposition (ALD) can also be used as a method for forming an inorganic layer. The ALD method is a method for forming a thin film in atomic layer units by alternately supplying the raw material gases of each element that constitutes the film to be formed to the surface on which the layer is to be formed. Although it has the disadvantage of a slow film formation speed, it has the advantage of being able to cover even surfaces with complex shapes neatly and to form a thin film with fewer defects than the plasma CVD method. In addition, the ALD method has the advantage that the film thickness can be controlled to the nano order, and it is relatively easy to cover a large surface. Furthermore, the ALD method is expected to improve the reaction rate, achieve low-temperature processing, and reduce unreacted gas by using plasma.
[0158] The thickness of the inorganic layer is not particularly limited, but for example, when the objective is to exhibit moisture-proof performance, it is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 20 nm or more. From the viewpoint of transparency and flexibility, the thickness of the inorganic layer is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less.
[0159] (Application) The laminate of the present embodiment is transparent, has excellent mechanical strength and dimensional stability, and can exhibit excellent durability even under high humidity conditions. For this reason, the laminate of the present embodiment is preferably used for optical members and substrates in various display devices, substrates for electronic devices, members for home appliances, window materials, interior materials, exterior materials for various vehicles and buildings, solar cell members, etc. EXAMPLES
[0160] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0161] <Production Example 1> (Phosphated pulp production) The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper. 2 A sheet-like pulp (with a Canadian Standard Freeness (CSF) of 700 mL when disintegrated and measured in accordance with JIS P 8121-2:2012) was used. This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to prepare 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 200 seconds to introduce phosphoric acid groups into the cellulose in the pulp, thereby obtaining a phosphorylated pulp.
[0162] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0163] Next, the washed phosphorylated pulp was subjected to an alkali treatment (neutralization treatment) as follows: First, the washed phosphorylated pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain phosphorylated pulp that had been subjected to an alkali treatment (neutralization treatment).
[0164] Next, the neutralized phosphorylated pulp was subjected to the above-mentioned washing treatment. The infrared absorption spectrum of the phosphorylated pulp thus obtained was measured using FT-IR. -1 Absorption due to the P=O of the phosphate group was observed near the nucleus, confirming that the phosphate group had been added to the pulp. In addition, when the obtained phosphorylated pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, confirming that it had cellulose type I crystals.
[0165] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated four times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion (A) containing fine fibrous cellulose.
[0166] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphate groups (amount of first dissociated acid) measured by the measurement method described below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0167] (Measurement of Phosphate Group Amount) The amount of phosphate groups in the fine fibrous cellulose (equivalent to the amount of phosphate groups in phosphorylated pulp) was measured by adding ion exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating it with ion exchange resin, and then titrating it with alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the slurry containing fine fibrous cellulose after the treatment with ion exchange resin, and measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 10). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated to obtain the amount of phosphate group (first dissociated acid amount) (mmol / g). The amount of alkali (mmol) required from the start of titration to the second end point was divided by the solid content (g) in the slurry to be titrated to obtain the total dissociated acid amount (mmol / g).
[0168] <Production Example 2> (Production of TEMPO oxidized pulp) As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. This raw material pulp was subjected to an alkaline TEMPO oxidation treatment as follows. First, the raw material pulp equivalent to 100 parts by mass of dry mass, 1.6 parts by mass of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and 10 parts by mass of sodium bromide were dispersed in 10,000 parts by mass of water. Next, a 13% by mass aqueous solution of sodium hypochlorite was added to 3.8 mmol per 1.0 g of pulp to start the reaction. During the reaction, a 0.5 M aqueous solution of sodium hydroxide was added dropwise to keep the pH at 10 to 10.5, and the reaction was deemed to be complete when no change in pH was observed.
[0169] The TEMPO oxidized pulp was then washed. The washing was performed by dehydrating the pulp slurry after TEMPO oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0170] The amount of carboxyl groups in the TEMPO oxidized pulp obtained was 1.30 mmol / g, as measured by the method described below. When the obtained TEMPO oxidized pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, and it was confirmed that the pulp contained cellulose type I crystals.
[0171] (Defibrillation process) Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated four times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (B) containing fine fibrous cellulose. X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of carboxyl groups measured by the measurement method described below was 1.30 mmol / g.
[0172] (Measurement of Carboxylic Acid Group Amount) The amount of carboxyl groups in the fine fibrous cellulose (equivalent to the amount of carboxyl groups in the TEMPO oxidized pulp) was measured by adding ion exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating the dispersion with ion exchange resin, and then titrating the dispersion with alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to a 0.2% by mass slurry containing fine fibrous cellulose, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. In addition, the titration using an alkali was performed by measuring the change in the pH value of the slurry while adding 0.1N aqueous sodium hydroxide to the fibrous cellulose-containing slurry after the treatment with the ion exchange resin. When the change in pH was observed while adding the aqueous sodium hydroxide, a titration curve as shown in FIG. 11 was obtained. As shown in FIG. 11, in this neutralization titration, a point was observed where the increment (differential value of pH with respect to the amount of alkali added) was maximum in the curve plotting the measured pH against the amount of alkali added. This maximum point of the increment is called the first end point. Here, the region from the start of the titration to the first end point in FIG. 11 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used for the titration. The amount of alkali required in the first region of the titration curve (mmol) was divided by the solid content (g) in the fine fibrous cellulose-containing slurry to be titrated to calculate the amount of carboxyl groups introduced (mmol / g). The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) (hereinafter referred to as the amount of carboxy groups (acid type)) per gram of mass of fibrous cellulose.
[0173] <Production Example 3> (Production of Phosphosphite Pulp) A phosphited pulp was obtained by carrying out the same operation as in Production Example 1, except that 33 parts by mass of phosphorous acid (phosphonic acid) was used instead of ammonium dihydrogen phosphate.
[0174] The infrared absorption spectrum of the phosphorous pulp obtained was measured using FT-IR. -1 Absorption due to the P=O of the phosphonic acid group, which is a tautomer of the phosphorous acid group, was observed near the nucleus, confirming that the phosphorous acid group (phosphonic acid group) was added to the pulp. In addition, when the obtained phosphorous-containing pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, confirming that it has cellulose type I crystals.
[0175] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorous-substituted pulp to prepare a slurry having a solid content concentration of 2% by mass. This slurry was treated four times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (C) containing fine fibrous cellulose. X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphorous groups (amount of first dissociated acid) measured by the measurement method described below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.
[0176] (Measurement of Phosphite Group Amount) The amount of phosphorous groups in the fine fibrous cellulose (equivalent to the amount of phosphorous groups in the phosphorous-sulfated pulp) was measured by adding ion-exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating the dispersion with ion-exchange resin, and then titrating the dispersion with alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the slurry containing fine fibrous cellulose after the treatment with ion exchange resin, and measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 10). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated to obtain the amount of phosphorous acid group (first dissociated acid amount) (mmol / g). The amount of alkali (mmol) required from the start of titration to the second end point was divided by the solid content (g) in the slurry to be titrated to obtain the total dissociated acid amount (mmol / g).
[0177] <Example 1> (Formation of fine fibrous cellulose sheets) Using the fine fibrous cellulose dispersion (A), a finished paper with a basis weight of 200 g / m was prepared by the method described in REP 2014 / 196357. 2 Thus, a fine fibrous cellulose-containing sheet of 100 g was obtained.
[0178] (Manufacture of laminates) A flat mold for injection molding (size of the cavity when clamped: length 280 mm, width 80 mm, thickness 4 mm) in which a concave and convex mold are combined to form a cavity was set on an injection molding tester (Nissei Plastic Industrial Co., Ltd., NEX140). The fine fibrous cellulose-containing sheet was cut to a length of 170 mm and a width of 75 mm. Next, the cut fine fibrous cellulose-containing sheet was fixed in the mold by a clamp mechanism installed at the end of the center plane in the thickness direction of the cavity formed by the two molds. At this time, the mold was arranged so that the length and width directions of the mold plane overlap with the center lines of the fine fibrous cellulose-containing sheet in the length and width directions, and the mold plane and the fine fibrous cellulose-containing sheet were parallel. After the fine fibrous cellulose-containing sheet was fixed, the mold was closed, and molten polycarbonate resin (Iupilon S-3000, manufactured by Mitsubishi Engineering Plastics) was injected into the mold under the conditions of a mold temperature of 110°C and a resin temperature of 290°C (at this time, the polycarbonate resin was injected onto both sides of the fine fibrous cellulose-containing sheet). The mold temperature was then lowered to 60°C to solidify the polycarbonate resin. By the above procedure, a laminate in which the fine fibrous cellulose-containing sheet (CNF sheet) was encapsulated in the resin component was obtained.
[0179] Fig. 2(a) is a schematic diagram for explaining the configuration of the laminate obtained in Example 1. Fig. 3(a) is a cross-sectional view of the laminate obtained in Example 1, showing the layer configuration in a cross section parallel to the length direction (direction L in Fig. 2(a)). Fig. 3(b) is a cross-sectional view of the laminate obtained in Example 1, showing the layer configuration in a cross section parallel to the width direction (direction W in Fig. 2(a)). Note that the cross section is a plane passing through the center point of the laminate, and is a plane that appears when cut in the thickness direction.
[0180] <Example 2> In the production of the laminate of Example 1, the same procedure as in Example 1 was repeated, except that when the fine fibrous cellulose-containing sheet was fixed in the mold, the length and width directions of the mold plane were overlapped with the length and width center lines of the fine fibrous cellulose-containing sheet, and when the mold was closed, the fine fibrous cellulose-containing sheet was positioned 500 μm inward in the thickness direction from the concave mold plane (the surface forming the void portion), to obtain a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component. Fig. 4(a) is a cross-sectional view of the laminate obtained in Example 2, showing the layer structure in a cross section parallel to the length direction, and Fig. 4(b) is a cross-sectional view of the laminate obtained in Example 2, showing the layer structure in a cross section parallel to the width direction.
[0181] <Example 3> (Manufacture of laminates) A flat mold for injection molding (size of the void when clamped: length 280 mm, width 80 mm, thickness 4 mm) was set on an injection molding tester (manufactured by Nissei Plastic Industrial Co., Ltd., NEX140) in which a concave mold and a convex mold were combined to form a void portion. The fine fibrous cellulose-containing sheet obtained in Example 1 was cut to a length of 170 mm and a width of 75 mm. Next, the fine fibrous cellulose-containing sheet after cutting was superimposed on a polycarbonate resin sheet (manufactured by Teijin Co., Ltd., Panlite PC-2151, thickness 200 μm) cut to a length of 180 mm and a width of 80 mm so that the center points of each were aligned. Then, this laminated sheet was fixed with heat-resistant tape on the concave mold plane (void portion forming surface). At this time, the polycarbonate resin sheet was placed so that it was in contact with one of the concave mold planes (void forming surface), and the longitudinal end of the polycarbonate resin sheet was aligned with a position 50 mm inside from the longitudinal end of the concave mold plane. Then, the mold was closed, and molten polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, Iupilon S-3000) was injected into the mold under the conditions of a mold temperature of 110 ° C and a resin temperature of 290 ° C (at this time, the polycarbonate resin was injected onto one side of the fine fibrous cellulose-containing sheet). Furthermore, the mold temperature was lowered to 60 ° C, and the polycarbonate resin was solidified. By the above procedure, a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 5(a) is a cross-sectional view of the laminate obtained in Example 3, showing the layer structure in a cross section parallel to the length direction, and Fig. 5(b) is a cross-sectional view of the laminate obtained in Example 3, showing the layer structure in a cross section parallel to the width direction.
[0182] <Example 4> (Formation of fine fibrous cellulose sheets) In the sheeting of the fine fibrous cellulose in Example 1, the finished sheet had a basis weight of 100 g / m 2 The other procedures were the same as above to obtain a fine fibrous cellulose-containing sheet. 2 Another fine fibrous cellulose-containing sheet of this type was prepared.
[0183] (Lamination of surface treatment layers) In the same manner as in laminating the surface-treated layers in Example 1, two fine fibrous cellulose-containing sheets each having a surface-treated layer laminated on both sides thereof were obtained.
[0184] (Manufacture of laminates) A flat mold for injection molding (size of the void when clamped: length 280 mm, width 80 mm, thickness 4 mm) was set on an injection molding tester (Nissei Plastic Industrial Co., Ltd., NEX140), which combines a concave mold and a convex mold to form a void. In addition, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 75 mm. Next, each of the cut fine fibrous cellulose-containing sheets was superimposed on two polycarbonate resin sheets (Teijin Co., Ltd., Panlite PC-2151, thickness 200 μm) cut to a length of 180 mm and a width of 80 mm, so that the center points were aligned. Then, these two laminated sheets were fixed with heat-resistant tape on a pair of mold planes (void forming surfaces). At this time, the polycarbonate resin sheet was placed so that it was in contact with each mold plane (void forming surface), and the longitudinal end sides of the polycarbonate resin sheet were aligned at a position 50 mm from the longitudinal end side of the concave mold plane and at a position 50 mm from the longitudinal end side of the convex mold plane (convex upper plane). After that, the mold was closed, and molten polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Corporation, Iupilon S-3000) was injected into the mold under conditions of a mold temperature of 110 ° C and a resin temperature of 290 ° C (at this time, the polycarbonate resin was injected between the fine fibrous cellulose-containing sheets). Furthermore, the mold temperature was lowered to 60 ° C, and the polycarbonate resin was solidified. By the above procedure, a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 7(a) is a cross-sectional view of the laminate obtained in Example 4, showing the layer structure in a cross section parallel to the length direction, and Fig. 7(b) is a cross-sectional view of the laminate obtained in Example 4, showing the layer structure in a cross section parallel to the width direction.
[0185] <Example 5> In the production of the laminate of Example 4, molten polycarbonate / acrylic alloy resin (Iupilon MB6001UR, manufactured by Mitsubishi Engineering Plastics Corporation) was injected into the mold instead of the polycarbonate resin. The other procedures were the same as those of Example 4, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 7(a) is a cross-sectional view of the laminate obtained in Example 5, showing the layer structure in a cross section parallel to the length direction, and Fig. 7(b) is a cross-sectional view of the laminate obtained in Example 5, showing the layer structure in a cross section parallel to the width direction.
[0186] <Example 6> In the sheeting of the fine fibrous cellulose in Example 4, the finished sheet had a basis weight of 200 g / m 2 The other procedures were the same as in Example 4, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 12(a) is a cross-sectional view of the laminate obtained in Example 6, showing the layer structure in a cross section parallel to the length direction, and Fig. 12(b) is a cross-sectional view of the laminate obtained in Example 6, showing the layer structure in a cross section parallel to the width direction.
[0187] <Example 7> In the production of the laminate of Example 6, molten polycarbonate / acrylic alloy resin (Iupilon MB6001UR, manufactured by Mitsubishi Engineering Plastics Corporation) was injected into the mold instead of the polycarbonate resin. The other procedures were the same as those of Example 6, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 12(a) is a cross-sectional view of the laminate obtained in Example 7, showing the layer structure in a cross section parallel to the length direction, and Fig. 12(b) is a cross-sectional view of the laminate obtained in Example 7, showing the layer structure in a cross section parallel to the width direction.
[0188] <Example 8> In the production of the laminate of Example 7, a polycarbonate / acrylic alloy resin sheet (manufactured by Mitsubishi Gas Chemical Company, Inc., thickness 200 μm) was used instead of the polycarbonate resin sheet. The other procedures were the same as in Example 7, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 12(a) is a cross-sectional view of the laminate obtained in Example 8, showing the layer structure in a cross section parallel to the length direction, and Fig. 12(b) is a cross-sectional view of the laminate obtained in Example 8, showing the layer structure in a cross section parallel to the width direction.
[0189] <Example 9> In the sheeting of the fine fibrous cellulose of Example 8, the fine fibrous cellulose dispersion (B) was used instead of the fine fibrous cellulose dispersion (A). The other procedures were the same as in Example 8, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 12(a) is a cross-sectional view of the laminate obtained in Example 9, showing the layer structure in a cross section parallel to the length direction, and Fig. 12(b) is a cross-sectional view of the laminate obtained in Example 9, showing the layer structure in a cross section parallel to the width direction.
[0190] <Example 10> In the sheeting of the fine fibrous cellulose of Example 8, the fine fibrous cellulose dispersion (C) was used instead of the fine fibrous cellulose dispersion (A). The other procedures were the same as in Example 8, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 12(a) is a cross-sectional view of the laminate obtained in Example 10, showing the layer structure in a cross section parallel to the length direction, and Fig. 12(b) is a cross-sectional view of the laminate obtained in Example 10, showing the layer structure in a cross section parallel to the width direction.
[0191] <Example 11> In the production of the laminate of Example 8, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 8 to obtain a laminate. In this laminate, the edge of the sheet containing fine fibrous cellulose was exposed without being encapsulated in the resin component. Next, in the laminate, a molten polyamide resin (Hakko Co., Ltd., hot melt adhesive No. 810) was applied to the exposed edge of the fine fibrous cellulose-containing sheet using a hot melt applicator (Hakko Co., Ltd., HAKKO MELTER 804). At this time, the thickness of the polyamide resin applied was set to 2 mm. By the above procedure, a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 9(a) is a cross-sectional view of the laminate obtained in Example 11, showing the layer structure in a cross section parallel to the length direction, and Fig. 9(b) is a cross-sectional view of the laminate obtained in Example 11, showing the layer structure in a cross section parallel to the width direction.
[0192] <Example 12> In the production of the laminate of Example 1, a polycarbonate resin sheet (Teijin Ltd., Panlite PC-2151, thickness 200 μm) was fixed to the concave mold plane (void forming surface) and the convex mold plane (void forming surface) with heat-resistant tape, respectively. At this time, the longitudinal end sides of the polycarbonate resin sheet were arranged so as to coincide with the position 50 mm from the longitudinal end side of the concave mold plane and the position 50 mm from the longitudinal end side of the convex mold plane (convex upper plane). The other procedures were the same as in Example 1, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 8(a) is a cross-sectional view of the laminate obtained in Example 12, showing the layer structure in a cross section parallel to the length direction, and Fig. 8(b) is a cross-sectional view of the laminate obtained in Example 12, showing the layer structure in a cross section parallel to the width direction.
[0193] <Example 13> In the production of the laminate of Example 2, another fine fibrous cellulose-containing sheet was placed so as to face the sheet in the thickness direction in the mold. When this fine fibrous cellulose-containing sheet was fixed in the mold, the length and width directions of the concave mold plane and the center lines of the fine fibrous cellulose-containing sheet in the length and width directions were overlapped, and the fine fibrous cellulose-containing sheet was placed at a position 500 μm away from each mold plane (void forming surface) on the inside in the thickness direction when the mold was closed. The other procedures were the same as in Example 2, and a laminate in which the fine fibrous cellulose-containing sheet was encapsulated in the resin component was obtained. Fig. 6(a) is a cross-sectional view of the laminate obtained in Example 13, showing the layer structure in a cross section parallel to the length direction, and Fig. 6(b) is a cross-sectional view of the laminate obtained in Example 13, showing the layer structure in a cross section parallel to the width direction.
[0194] <Comparative Example 1> In the production of the laminate of Example 1, the fine fibrous cellulose-containing sheet was not placed in the mold. The other procedures were the same as in Example 1, and a molded body made of only polycarbonate resin was obtained. Fig. 13(a) is a cross-sectional view of the laminate obtained in Comparative Example 1, showing the layer structure in a cross section parallel to the length direction, and Fig. 13(b) is a cross-sectional view of the laminate obtained in Comparative Example 1, showing the layer structure in a cross section parallel to the width direction.
[0195] <Comparative Example 2> In the production of the laminate of Example 1, the fine fibrous cellulose-containing sheet was cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 1 to obtain a laminate. In this laminate, the edge of the fine fibrous cellulose-containing sheet was exposed without being encapsulated in the resin component. Fig. 14(a) is a cross-sectional view of the laminate obtained in Comparative Example 2, showing the layer structure in a cross section parallel to the length direction, and Fig. 14(b) is a cross-sectional view of the laminate obtained in Comparative Example 2, showing the layer structure in a cross section parallel to the width direction.
[0196] <Comparative Example 3> In the production of the laminate of Example 2, the fine fibrous cellulose-containing sheet was cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 2 to obtain a laminate. In this laminate, the edge of the fine fibrous cellulose-containing sheet was exposed without being encapsulated in the resin component. Fig. 15(a) is a cross-sectional view of the laminate obtained in Comparative Example 3, showing the layer structure in a cross section parallel to the length direction, and Fig. 15(b) is a cross-sectional view of the laminate obtained in Comparative Example 3, showing the layer structure in a cross section parallel to the width direction.
[0197] <Comparative Example 4> In the production of the laminate of Example 3, the fine fibrous cellulose-containing sheet was cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 3 to obtain a laminate. In this laminate, the edge of the fine fibrous cellulose-containing sheet was exposed without being encapsulated in the resin component. Fig. 16(a) is a cross-sectional view of the laminate obtained in Comparative Example 4, showing the layer structure in a cross section parallel to the length direction, and Fig. 16(b) is a cross-sectional view of the laminate obtained in Comparative Example 4, showing the layer structure in a cross section parallel to the width direction.
[0198] <Comparative Example 5> In the production of the laminate of Example 4, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 4 to obtain a laminate. In this laminate, the edge of the sheet containing fine fibrous cellulose was exposed without being encapsulated in the resin component. Fig. 17(a) is a cross-sectional view of the laminate obtained in Comparative Example 5, showing the layer structure in a cross section parallel to the length direction, and Fig. 17(b) is a cross-sectional view of the laminate obtained in Comparative Example 5, showing the layer structure in a cross section parallel to the width direction.
[0199] <Comparative Example 6> In the production of the laminate of Example 5, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 5 to obtain a laminate. In this laminate, the edge of the sheet containing fine fibrous cellulose was exposed without being encapsulated in the resin component. Fig. 17(a) is a cross-sectional view of the laminate obtained in Comparative Example 6, showing the layer structure in a cross section parallel to the length direction, and Fig. 17(b) is a cross-sectional view of the laminate obtained in Comparative Example 6, showing the layer structure in a cross section parallel to the width direction.
[0200] <Comparative Example 7> In the production of the laminate of Example 6, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 6 to obtain a laminate. In this laminate, the edges of the sheets containing fine fibrous cellulose were exposed without being encapsulated in the resin component. Fig. 18(a) is a cross-sectional view of the laminate obtained in Comparative Example 7, showing the layer structure in a cross section parallel to the length direction, and Fig. 18(b) is a cross-sectional view of the laminate obtained in Comparative Example 7, showing the layer structure in a cross section parallel to the width direction.
[0201] <Comparative Example 8> In the production of the laminate of Example 7, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 7 to obtain a laminate. In this laminate, the edge of the sheet containing fine fibrous cellulose was exposed without being encapsulated in the resin component. Fig. 18(a) is a cross-sectional view of the laminate obtained in Comparative Example 8, showing the layer structure in a cross section parallel to the length direction, and Fig. 18(b) is a cross-sectional view of the laminate obtained in Comparative Example 8, showing the layer structure in a cross section parallel to the width direction.
[0202] <Comparative Example 9> In the production of the laminate of Example 8, two sheets containing fine fibrous cellulose were cut to a length of 170 mm and a width of 80 mm. The other procedures were the same as in Example 8 to obtain a laminate. In this laminate, the edges of the sheets containing fine fibrous cellulose were exposed without being encapsulated in the resin component. Fig. 18(a) is a cross-sectional view of the laminate obtained in Comparative Example 9, showing the layer structure in a cross section parallel to the length direction, and Fig. 18(b) is a cross-sectional view of the laminate obtained in Comparative Example 9, showing the layer structure in a cross section parallel to the width direction.
[0203] <Evaluation> (Flexural modulus) Test pieces measuring 80 mm in length and 10 mm in width were cut out from the laminate and the molded product (Comparative Example 1). The laminate was cut out from the portion where the fine fibrous cellulose-containing sheet was present. Using the test pieces, a bending test was performed using a universal material testing machine (Tensilon RTC-1250A, manufactured by A&D Co., Ltd.) in accordance with JIS K 7171:2016 under the conditions of a support distance of 64 mm and a deflection rate of 2 mm / min. The test temperature was 23°C. The flexural modulus (GPa) was calculated from the slope of the stress-strain curve between strains of 0.0005 and 0.0025.
[0204] (coefficient of linear thermal expansion) Test pieces measuring 50 mm in length and 10 mm in width were cut out from the laminate and the molded product (Comparative Example 1). For the laminate, the cutout was made from the portion where the fine fibrous cellulose-containing sheet was present. Using this test piece, a thermomechanical analyzer (Seiko Instruments Inc., TMA / SS6100) was used to measure the change in length of the test piece under conditions of a temperature range of 23 to 90°C and a heating rate of 5°C / min, and the linear thermal expansion coefficient (ppm / K) was calculated by dividing the change in length in a temperature range of 30 to 80°C by the change in temperature.
[0205] (yellowness) Test pieces of 50 mm square were cut out from the laminate and the molded product (Comparative Example 1). The laminate was cut out from the part where the fine fibrous cellulose-containing sheet was present. The test pieces were used to measure the yellowness using a color meter (Colour Cute i, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K 7373:2006.
[0206] (warp) The laminate and the molded product (Comparative Example 1) were left to stand for 24 hours in an environment with a temperature of 23° C. and a relative humidity of 50%. Thereafter, the laminate and the molded product were observed, and the degree of warping was evaluated according to the following criteria. A: The laminate (molded product) is not curved and maintains its flat shape. B: The laminate (molded product) shows slight curvature, but generally maintains a flat plate shape. C: The laminate (molded product) was significantly curved and did not maintain its flat shape.
[0207] (durability) The laminate and the molded product (Comparative Example 1) were immersed for 24 hours in warm water at a temperature of 60° C. Thereafter, the laminate and the molded product were observed and evaluated for durability according to the following criteria. A: No change in appearance was observed in the laminate (molded product), and the laminate structure and flat plate shape were maintained. B: Laminate (molded product) There is a slight change in appearance, but the laminate structure and flat plate shape are generally maintained. C: The laminate (molded product) had a significant change in appearance, and the laminate structure and flat plate shape were not maintained.
[0208] [Table 1]
[0209] [Table 2]
[0210] [Table 3]
[0211] As is clear from Table 1, the laminates obtained in the examples had improved flexural modulus, reduced coefficient of linear thermal expansion, and excellent durability. In particular, in Example 2, in which the fine fibrous cellulose-containing sheet was arranged in the surface layer vicinity region, the effect of improving the bending modulus was greater than that of Example 1. In Example 2, a slight decrease in durability was observed, but in Example 3, in which a resin sheet was arranged in the outermost layer of the laminate and a fine fibrous cellulose-containing sheet was laminated on the resin sheet, the durability was better. In addition, in Examples 2 and 3, slight warping was observed in the laminate, but in Example 4, in which the fine fibrous cellulose-containing sheet was arranged in the surface layer vicinity region of both planes, warping was suppressed and the effect of improving the bending modulus was even greater. On the other hand, in the laminates of Comparative Examples 2 to 9, in which the edges of the fine fibrous cellulose-containing sheets were exposed from the resin material, the durability quality was significantly reduced.
[0212] In Examples 5, 7, and 8, in which a polycarbonate / acrylic alloy resin was used as the resin material, superior flexural modulus and linear thermal expansion coefficient were exhibited. Furthermore, in Examples 8 and 10, in which phosphorylation or subphosphitylation was used as the method for modifying the fine fibrous cellulose, the yellowness of the laminate was kept low compared to Example 9, in which TEMPO oxidation was used.
[0213] <Evaluation> (Flexural modulus at high temperatures) The flexural modulus at high temperatures was measured for the laminate obtained in Example 8 by the following procedure. A test piece measuring 80 mm in length and 10 mm in width was cut out from the part of the laminate where the fine fibrous cellulose-containing sheet was present. Using this test piece, a bending test was performed using a universal material testing machine (Tensilon RTC-1250A, manufactured by A&D Co., Ltd.) under the conditions of a support distance of 64 mm and a deflection rate of 2 mm / min in accordance with JIS K 7171:2016, except that the test temperature was 80°C. The flexural modulus (GPa) was calculated from the slope of the stress-strain curve between strains of 0.0005 and 0.0025. The calculated flexural modulus was 4.3 GPa, and it was confirmed that the flexural modulus was maintained even at high temperatures.
[0214] (Durability under high temperatures) Furthermore, the laminate obtained in Example 8 was evaluated for durability at high temperatures by the following procedure. The laminate was left to stand in a thermostatic chamber at 110°C in an air atmosphere for 720 hours, and then the appearance of the laminate was observed. No significant change was observed in the appearance of the laminate, and the interlayer adhesion was maintained, confirming that the durability at high temperatures was good. [Explanation of symbols]
[0215] 10. Fine fibrous cellulose-containing sheet 20 Resin sheet 30 Resin layer 30a Molten Resin 35 Coating resin 50 Mold 51 Inlet 52 Fixing member 100 Laminate 101 Molded body
Claims
1. Injecting a molten resin into a mold in which a sheet containing fibrous cellulose having a fiber width of 1000 nm or less is disposed; and solidifying the molten resin, The method for producing a laminate, wherein in the laminate, the sheet containing the fibrous cellulose is in a state of being encapsulated by a resin component.
2. The method for producing a laminate according to claim 1 , wherein the fibrous cellulose is unevenly distributed in a non-exposed region that is a region near a surface layer in a thickness direction of the laminate.
3. In the step of injecting the molten resin, the sheets containing the fibrous cellulose are disposed along both sides of the inner wall of a mold so as to face each other, The method for producing a laminate according to claim 1 or 2, wherein at least a portion of the molten resin is filled between opposing sheets containing the fibrous cellulose.
4. The method for producing a laminate according to any one of claims 1 to 3, wherein in the step of injecting the molten resin, the sheet containing the fibrous cellulose is fixed to an inner wall of a mold via a resin sheet.
5. The method for producing a laminate according to any one of claims 1 to 4, wherein the area of a maximum surface of the laminate is larger than the area of a maximum surface of the sheet containing fibrous cellulose.
6. The method for producing a laminate according to any one of claims 1 to 5, wherein in the laminate, edges of the sheets containing the fibrous cellulose are encapsulated with a resin component derived from the molten resin.
7. The method for producing a laminate according to any one of claims 1 to 6, further comprising the step of covering exposed portions of the sheet containing fibrous cellulose after the step of solidifying the molten resin.
8. The method for producing a laminate according to any one of claims 1 to 7, wherein the molten resin contains an alloy resin containing a polycarbonate resin and an acrylic resin.
Citation Information
Patent Citations
Polycarbonate resin / cellulose fiber laminate and method for producing the same
JP2010023275A
Molded article with excellent mechanical characteristic, and method and apparatus for manufacturing the same
JP2012207100A
Method for producing molded body, and injection / compression molded body
JP2016203419A
Housing and method for manufacturing housing
JP2017170829A
Fiber-resin composite body and method for producing the same
JP2017222786A